Cystic Duct Stump Clearance with Distal Clipping and Proximal Sweeping (DCPS) Technique in Laparoscopic Cholecystectomy: A Cross-Sectional Study - Abro, Kanwal Nisa; Ashraf, Fariha; Batool, Sehrish; Jawed, Soura; Murtaza, Ghulam (Indus Journal of Bioscience Research, 2025)
Background: After laparoscopic cholecystectomy (LC) for Cholelithiasis, persistence of the symptoms may occur in 5% of patients. The cystic duct remnant calculus can be one of the causes. Distal clipping and proximal sweeping (DCPS) are one of the methods to clear cystic duct. Objective: To determine the proportion of patients who achieve clearance of the cystic duct stump from stones or sludge using the Distal Clipping and Proximal Sweeping (DCPS) technique during LC. Methods: This cross-sectional study was conducted on patients undergoing LC by a consultant general surgeon or a registrar under supervision, in the Department of General Surgery at a tertiary care hospital in Karachi, Pakistan, from February to December 2023. The intra-operative DCPS technique involves achieving the critical view of safety, clipping the cystic duct at its junction with the Hartmann’s pouch (distal clipping), making a small incision proximally towards the CBD, and gently sweeping the common bile duct (CBD) and cystic duct towards incision to clear any sludge or stones in the cystic duct stump. Results: A total of 174 Patients were enrolled in the study with the mean age of 47.11 ±14.37. There was a female predominance 103 (59.2%) and 99 patients had co-morbidities. Mean ± SD Duration of Surgery in all patients was 76.59 ±20.62 minutes from incision to dressing. DCPS was positive in 84 patients (48.2%) for stone/sludge; 26 (14.9%) for stones and 58 (33.3%) for sludge. None of the patient had any CBD injury or iatrogenic complete cystic duct transaction or avulsion intra-operatively. None of the patient was found to have post-operative leak and readmission because of any complications of DCPS. Conclusion: DCPS can be performed safely during LC to clear cystic duct from stone/sludge.